Análisis de la incidencia entre el crecimiento económico, la globalización cultural, la globalización política, el desarrollo financiero y el gasto del gobierno con el desempleo de Ecuador, durante 1990- 2022. - Narváez Guarderas, Dayana Nicol (2025)
In Ecuador, the unemployment rate has not shown improvement in the post-pandemic period, remaining unchanged at 3.8% in both 2019 and 2022, a stability in unemployment rates affecting approximately 324,904 people. Around this, the general objective of the study is to evaluate the relationship between economic growth, cultural globalization, political globalization, financial development and government spending with unemployment in Ecuador during 1990-2022, using statistical and econometric techniques in order to recommend mechanisms to reduce unemployment. Data sources from the World Bank, the Swiss Economic Institute [KOF] and the International Monetary Fund [IMF] have been used, considering the application of cointegration and spectral causality tests for time series modeling. The results show that there are short and long term relationships between the variables associated with explaining unemployment. In addition, a bidirectional causal relationship was found to exist between cultural globalization and unemployment, while a unidirectional causal relationship in the direction of unemployment to government spending was verified. The policy implications for Ecuador suggest a policy of economic diversification and trade liberalization in conjunction with tax incentives for reinvestment initiatives for business development and growth that promote new formal jobs and training programs. At the same time, low-cost financing mechanisms aimed at MSMEs and entrepreneurship are suggested. Similarly, public-private partnerships for infrastructure to development, effective state regulation and the implementation of technical education and dual training programs should be considered to mitigate the unemployment problem in the country.